Allergic Contact Dermatitis From Chamomile Plant - Özden, Müge Güler; Denizli, H.; Aydin, F.; Şentürk, N.; Cantürk, T.; Turanli, A.Y. (My University, 2011)
Herbal remedies for cosmetic and health-promoting purposes are getting more popular in worldwide. The Compositae (Asteraceae) family of plants is currently an important cause of allergic plant contact dermatitis in Europe. A 55-year-old woman presented with erythema, edema and vesiculobullous lesions over her knees caused by Chamomile. Patch testing with chamomile was positive. The patient has been diagnosed as allergic contact dermatitis. We report a first case of contact dermatitis caused by German chamomile from our country. © 2011 OMU All rights reserved.
Keywords: Allergic Contact Dermatitis; Astraceae; Chamomile; Compositae; Herbal; Patch Test